2009
DOI: 10.1002/clc.20570
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Prognosis of Non‐Interventionally Followed Patients with Isolated Myocardial Bridge and Severe Systolic Compression of the Left Anterior Descending Coronary Artery

Abstract: Purpose: The aim of this study was to investigate the long-term prognosis of non-interventionally followed patients with myocardial bridge and angiographic milking of the left anterior descending (LAD) coronary artery. Methods: All of the coronary angiography records from May 2000 to November 2007 were reevaluated and patients who had more than 70% narrowing during systole on LAD were eligible for the present study. Follow-up was carried out by physical examination, echocardiography, and treadmill exercise tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
0
21
0
2
Order By: Relevance
“…Previous prospective studies mainly focused on the significance of isolated ICA in the absence of atherosclerosis in the nonbridging arteries [8][9][10] or with small sample sizes. 2,3,11 The results were quite discordant; some showed that ICA is a benign anatomic variation, 2,3,10,11 and others showed it as an anatomic risk factor for CAD. 8,9 Recently, multidetector computed tomography (MDCT) has been used noninvasively to examine coronary arteries directly, and surprisingly, the wide use of MDCT also increased the detection rate for ICA.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 99%
“…Previous prospective studies mainly focused on the significance of isolated ICA in the absence of atherosclerosis in the nonbridging arteries [8][9][10] or with small sample sizes. 2,3,11 The results were quite discordant; some showed that ICA is a benign anatomic variation, 2,3,10,11 and others showed it as an anatomic risk factor for CAD. 8,9 Recently, multidetector computed tomography (MDCT) has been used noninvasively to examine coronary arteries directly, and surprisingly, the wide use of MDCT also increased the detection rate for ICA.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 99%
“…9 The magnitude of the compressive force exerted by the MB on the coronary artery is closely related to the contractile force of the MB muscle, which is distinctly associated with the anatomical properties of the MB, namely, its length, 20 thickness, 29,57 and location. 58 In fact, coronary angiography combined with IVUS reveals that a longer MB has a significant association with more severe systolic compression, 20 and MDCT shows that the thickness of MB correlates with the severity of systolic compression. 29, 57 In hypertrophic hearts, a long MB also leads to significant LAD compression, 14 and a deeply situated intramyocardial LAD with a thick MB is associated with sudden cardiac death.…”
Section: Direct Compression Of the Lad By The Mbmentioning
confidence: 99%
“…Although MB is generally considered a benign anomaly, it may be associated with clinical manifestations that have been linked to dynamic compression [5][6][7][8][9][10][11]. The treatment strategy is guided by the presence of reduced myocardial perfusion, which is closely related to extent of dynamic compression [18,19].…”
Section: Discussionmentioning
confidence: 99%